CHALLENGES AND POTENTIALS OF WAQF IN CONTEMPORARY INDONESIA - USWATUN HASANAH; HERU SUSETYO (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2020)
Waqf, as an instrument of the Islamic Economy, has been developed in a quite long period. Since the Prophet Muhammad PBUH era up to present. Indonesian people have also recognized waqf much long before Indonesian independence in 1945. Yet, the institutionalization of waqf into national law is less than five decades in Indonesia. As the most predominantly Muslim country in the world, most of the people recognize waqf only as a land donated in the name of Allah for building masjids, schools (madrasah) or cemeteries. Whereas, at The Law No. 41/ 2004 on Waqf, waqf is not limited to immovable goods but also movable assets. And, the utilization of waqf is not limited to build masjids and madrasah, but also for other purposes that related to public welfare. This article discusses the challenges and potentials of waqf in contemporary Indonesia